Pengaruh Pertumbuhan Tabungan, Deposito dan Kredit terhadap Profitabilitas pada Lembaga Perkreditan Desa (LPD) di Kecamatan Gianyar Periode Tahun 2015-2017 - Anak Agung Novita Dewi; Kompiang Bagiada; I Nyoman Senimantara (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2019)
The aims of this research is to find out how the effect of the growth of savings, deposits and credit simultaneously and partially on profitability at Lembaga Perkreditan Desa (LPD) in Gianyar District. The data analysis technique used is the classic assumption test and multiple linear regression analysis. The results of the study on the effect of growth in savings, deposits and credit have a significant effect on profitability at Lembaga Perkreditan Desa (LPD) in Gianyar District. The savings growth variable has a negative and not significant effect on profitability. The variable growth in deposits has a positive and significant effect on profitability. The variable credit growth has a positive and not significant effect on profitability.